Implications of the EU-SILC following rules, and their implementation, for longitudinal analysis - Maria Iacovou; Peter Lynn (University of Essex, Institute for Social and Economic Research (ISER), 2013)
This paper examines the following rules in the EU-SILC survey, in terms both of the wording of the regulations, and on how these regulations are interpreted and implemented. We pay particular attention to the percentages of the sample re-interviewed following household splits, and assess the implications of these on the suitability of the EU- SILC for longitudinal analysis of the effects of household splits. Using longitudinal data from the 2003 to 2010 UDBs, we find considerable variations in practice across the countries of the EU-SILC. Among households experiencing a split, large percentages of those remaining in the original sample household are followed, but only very low percentages of those moving to a split-off household. While this does not have a major impact on overall attrition rates, it does mean that the EU-SILC may not be suitable for longitudinal analysis of specific groups. Analysis of individuals leaving the family home following divorce or separation is particularly problematic, while analysis of young home-leavers is possible in a number of countries, though it should be undertaken with caution.
Keywords: 330; Survey methods; cross-national data; longitudinal analysis; following rules; EU-SILC